2018
DOI: 10.21873/anticanres.13002
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Treatment Modification in First-Line Metastatic Renal Cell Carcinoma: Analysis of the STAR-TOR Registry

Abstract: Background/Aim: Sunitinib is the current standard of care for first-line (1L) treatment of metastatic renal cell carcinoma (mRCC). Previous studies suggest that a modified treatment schedule may benefit patients. Our aim was to evaluate efficacy and safety regarding sunitinib treatment modification in 1L treatment of mRCC. Materials and Methods: Data were drawn from STAR-TOR, a German realworld registry to evaluate outcomes of patients with mRCC who received 1L sunitinib. Patients were divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
4
21
0
1
Order By: Relevance
“…However, the number of patients receiving 2/1 dosing was low (n = 32). A recent analysis of nearly 300 patients from a German registry found that, when compared with 4/2 dosing, sunitinib dose modification reduced the frequency of AEs and significantly increased mPFS (6.0 vs 15.1 months) and OS (13.7 vs 38.1 months) [57]. Notably, patients who received sunitinib dose modification were older, but had a more favorable risk status compared with patients receiving 4/2 dosing, which may explain why these measures fall outside the confidence estimates reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of patients receiving 2/1 dosing was low (n = 32). A recent analysis of nearly 300 patients from a German registry found that, when compared with 4/2 dosing, sunitinib dose modification reduced the frequency of AEs and significantly increased mPFS (6.0 vs 15.1 months) and OS (13.7 vs 38.1 months) [57]. Notably, patients who received sunitinib dose modification were older, but had a more favorable risk status compared with patients receiving 4/2 dosing, which may explain why these measures fall outside the confidence estimates reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…Since the survival of patients with metastatic kidney cancer is poor, a great amount of data from preclinical and clinical research has been gathered (14)(15)(16)(17)(18)(19). In addition to the development of new drugs, personalized treatment is another important approach.…”
Section: Discussionmentioning
confidence: 99%
“…Те же проблемы отмечаются в других странах БРИКС [8,13], в которых только 20 % больных получают вторую линию терапии. В немецком проспективном регистровом исследовании STAR-TOR [14] в группе, получившей последовательную терапию сунитинибом / темсиролимусом и затем акситинибом, медиана ОВ составила 38,1 месяца, а в группе, в которой назначалась только одна линия терапии, -13,7 месяца (P<0,0001). В чешском регистре RENIS назначение двух линий терапии приводило к медиане ОВ 29 месяцев, тогда как получение пациентами трех линий -к 50,9 месяца [15].…”
Section: Discussionunclassified